Community based programs to improve the oral health of Australian Indigenous adolescents: a systematic review and recommendations to guide future strategies - Josephine Gwynn; John Skinner; Yvonne Dimitropoulos; Angela Masoe; Boe Rambaldini; Vita Christie; Woosung Sohn; Kylie Gwynne (BMC, 2020)
Abstract Background To review the international literature on community-based interventions aiming to improve the oral health of Indigenous adolescents and identify which demonstrate a positive impact. Methods Data sources were MEDLINE, EMBASE, CINAHL, SCOPUS, the COCHRANE library and the Australian Indigenous HealthInfoNet. Articles were included where they: were published in English from 1990 onwards; described oral health outcomes for Indigenous adolescents aged 10 to 19 years; implemented a community based oral health intervention. The Quality Assessment Tool for Quantitative Studies from the Effective Public Health Practice Project was applied. Results Nine studies met inclusion criteria; two rated strong in quality; only one study was conducted with an urban community; five reported moderate community engagement. Five intervention strategies were identified, and schools were the most common setting reported. Statistically significant improvements were described in eight studies with the most frequently reported outcome being change in decayed missing or filled teeth. Conclusions Few good quality peer reviewed international studies of community-based oral health interventions which address the needs of Indigenous adolescents exist. Studies must include strong Indigenous community leadership and governance at all stages of the research, adopt participatory action-based research approaches, and are required in urban communities.